Predictive Role of Interleukin-18 in Liver Steatosis in Obese Children - Marta Flisiak-Jackiewicz; Anna Bobrus-Chociej; Eugeniusz Tarasów; Małgorzata Wojtkowska; Irena Białokoz-Kalinowska; Dariusz Marek Lebensztejn (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Interleukin-18 (IL-18) is a proinflammatory cytokine associated with metabolic syndrome (MS). Nonalcoholic fatty liver disease (NAFLD) can be recognized as a feature of MS. Material and Methods. Serum IL-18 concentration was evaluated in serum of 108 obese children, determined with ELISA, and referred to degree of liver steatosis in USG or total intrahepatic lipid content assessed by magnetic resonance proton spectroscopy (1HMRS). Results. Fatty liver was confirmed in 89 children with USG and in 72 with 1HMRS. IL-18 concentration demonstrated significantly higher values in patients than in controls. Significant correlations between IL-18 and ALT, GGT, triglycerides, hsCRP, and the degree of liver steatosis were demonstrated. NAFLD children had significantly higher level of IL-18, ALT, GGT, HOMA-IR, waist circumference, and total lipids content in 1HMRS than other obese children. IL-18 level was also significantly higher in obese children with advanced liver steatosis. Measurement of serum IL-18 showed ability to differentiate children with fatty liver from those without steatosis. Conclusion. Elevated serum IL-18 concentration and its correlation with hepatocyte injury, systemic inflammation, and degree of liver steatosis support role in NAFLD pathomechanism. IL-18 can be considered to play a role in predicting advanced liver steatosis and fatty liver in obese children.